The three commitments of leadership [ how clarity, stability, and rhythm create great leaders - Endersbe, Tom; Therrien, Jay; Wortmann, Jon (McGraw-Hill, 2012)
A compelling call to revolutionize the accepted principles of leadership by simplifying them. Explains how to improve leadership effectiveness by focusing on three simple commitments: Clarity, Stability, and Rhythm